Click Chemistry Approach: Regioselective One-pot Synthesis of Some New 8-Trifluoromethylquinoline Based 1,2,3-Triazoles as Potent Antimicrobial Agents - Hegde, Gurumurthy; Garudachari, B.; Isloor, Arun M.; Satyanarayana, M. N.; Fun, Hoong-Kun (Elsevier, 2014)
Three series of 8-trifluoromethylquinoline based 1,2,3-triazoles derivatives (5a–c, 6a–d and 7a–c) were synthesized by multi-step reactions by click chemistry approach. Synthesized compounds were characterized by spectral studies and X-ray analysis. The final compounds were screened for their in-vitro antimicrobial activity by well plate method (zone of inhibition). Compounds 5c, 6b, 8b, 11 and 12 were found to be active against tested microbial strains. The results are summarized in Tables 5 and 6.